2012
DOI: 10.1111/j.1467-9914.2012.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Wage and Productivity Differentials in Japan: The Role of Labor Market Mechanisms

Abstract: Two stylized facts characterized Japan during the so-called Lost Decade (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005): rising wage inequalities and increasing productivity di¤er-entials at the …rm level. Surprisingly, these features have never been connected in the literature. This paper attempts to …ll this gap by proposing an explanation focusing on labor market mechanisms. We …rst construct an e¢ ciency wage model with two types of …rms distinguished by their job secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“…First, the increasing heterogeneity of the firms' employment policies may have an impact in term of (employment security and wages) inequalities from the point of view of workers. It may be an explanation of the increasing inequalities for regular workers, which are observed on the Japanese labor market since at least the beginning of the 1990s (Kalantzis et al, 2012). This point should be carefully studied.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…First, the increasing heterogeneity of the firms' employment policies may have an impact in term of (employment security and wages) inequalities from the point of view of workers. It may be an explanation of the increasing inequalities for regular workers, which are observed on the Japanese labor market since at least the beginning of the 1990s (Kalantzis et al, 2012). This point should be carefully studied.…”
Section: Resultsmentioning
confidence: 96%
“…It may explain why there is no agreement about the nature of the current evolution characterizing the Japanese economic system. Second, this increasing diversity of firms may be the background of rising inequalities, as shown for example by Kalantzis, Kambayashi & Lechevalier (2012), who link productivity dispersion to wage inequalities in the case of Japan. What has been just said in general terms is particularly important in the case of the evaluation of changes on the Japanese labor market. From the mid-1990s, there have been several studies questioning the "end of the Japanese employment system" (Sako & Sato, 1997;Genda & Rebick, 2000;Kato, 2001;Rebick, 2005, among many others).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, private sector's wage systems have shown that there is a shift toward performance‐ or ability‐based systems. Thus, MAA's pension with final salary system was not acceptable by private sector employees (Kalantzis et al ). Thus, the 1985 revision abolished the final salary system.…”
Section: History Of Maa Pension Reformmentioning
confidence: 99%
“…This duality is empirically analyzed by using a switching regression model inDickens and Lang (1985),Sakamoto and Chen (1991), andIshiwaka (1999) Kalantzis, Kambayashi, and Lechevalier (2012). shows the existence of this duality in the Lost Decade in Japan 3 Note that the duality in the labor market has another effect on macroeconomic models: Income distribution among classes.…”
mentioning
confidence: 99%